Increasing the Confiscation of Cigarette Taxable Goods through International Cooperation in the City of Batam: JEL Classification: F52, F55, H26, K42, O17 - Navisa Septia; Devita Prinanda; Havidz Ageng Prakoso (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
Batam, as an Indonesian Free Trade Zone (FTZ) bordering Singapore and Malaysia, faces persistent cross-border smuggling of illegal cigarettes that reduces state excise revenue. This study examines and compares the effectiveness of bilateral cooperation between Indonesia–Singapore (DJBC–SPCG MoU) and Indonesia–Malaysia (Patkor Kastima/JTFN) in strengthening customs enforcement against cigarette smuggling. A qualitative case study approach was employed using semi-structured interviews with officials from the Batam Customs and Excise Office, supported by enforcement reports, official cooperation documents, and relevant literature. The findings show that the Indonesia–Singapore cooperation generated the strongest short-term impact, increasing illegal cigarette seizures by 492% in 2025 through real-time intelligence sharing and faster operational responses. Meanwhile, cooperation with Malaysia significantly enhanced pre-border interceptions and expanded long-term operational coverage. Overall, both cooperation frameworks shifted customs enforcement from a reactive to an intelligence-driven cross-border approach. Strengthening interagency coordination and expanding track-and-trace technology are recommended to further reduce smuggling and protect national excise revenue.